A Comparative Study of Conventional and Conformal Cooling Systems for Injection Moulding of Acrylonitrile Butadiene Styrene Material - Alex Kong Pang Tong,; Aznizam Ahmad, (Progress in Engineering Application and Technology, 2025)
Injection moulding is one the most familiar processes for manufacturing of plastic parts by injecting molten thermoplastic polymers into a metal mould. In injection moulding process, the cooling channel performance is one of the most crucial factors because it has significant effect on both production rate and the quality of the plastic part. This study investigates the comparative performance of conventional and conformal cooling systems in the injection moulding process using acrylonitrile butadiene styrene (ABS) material of stainless steel mould. The study evaluates the effectiveness of different cooling channel configurations through simulation analysis using Solidworks Plastics 2022. Three conformal cooling channel diameters (4 mm, 6 mm, and 8 mm) were compared against a conventional cooling system with a 6 mm diameter channel. The study specifically examined cooling time, shrinkage and weight of the moulded parts as key performance indicators. Results demonstrated that the 4 mm diameter conformal cooling channel achieved the best performance, reducing cooling time by 4.5% (from 4.49 to 4.29 seconds) and decreasing volumetric shrinkage by 19.0% (from 0.4148% to 0.3361%) compared to the conventional system. Part mass remained relatively consistent across all configurations, with variations less than 0.2%. The 6 mm and 8 mm diameter conformal channels also showed improvements over the conventional system, though less pronounced than the 4 mm configuration. These findings suggest that properly designed conformal cooling channels, particularly those with smaller diameters, can significantly improve injection moulding efficiency and product quality.